Biodistribution of gold nanoparticles in vivo - Yu. A. Finogenova; A. A. Lipengolts; V. A. Skribitsky; K. E. Shpakova; A. V. Smirnova; N. N. Sycheva; E. Yu. Grigorieva (Сибирский научный медицинский журнал, 2025)
Gold nanoparticles have unique physical, chemical and optical properties, due to which they are used to develop promising drugs: radiosensitisers, X-ray contrast media, agents for photothermal therapy, drugs for targeted delivery. In each case, the choice of nanoparticle parameters is determined not only by the field of application, but also by the biodistribution in the living organism: blood circulation time and accumulation in target organs and tissues, including the tumor. For long blood circulation, nanoparticles should avoid phagocytosis by liver macrophages. The aim of this review was to systematise information on the influence of gold nanoparticle parameters on their pharmacokinetic properties and biodistribution in intact and tumor-bearing small laboratory animals. Size, shape and stabilising coating were considered. Smaller nanoparticles tend to circulate longer in the bloodstream and accumulate more slowly in the liver. Various coatings such as citrate, bovine serum albumin or polyethylene glycol are used to protect nanoparticles against aggregation, opsonisation and phagocytosis. The influence of nanoparticle shape on biodistribution is not completely understood; presumably, it is less important than size and coating. In general, the available data indicate that gold nanoparticles with a diameter of up to 50 nm with a polymer coating have optimal pharmacokinetic properties for biomedical application.